2000
DOI: 10.1063/1.125687
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial strain induced metal insulator transition in La0.9Sr0.1MnO3 and La0.88Sr0.1MnO3 thin films

Abstract: We are reporting an unexpected metal insulator transition at the ferromagnetic phase-transition temperature for thin films of La0.9Sr0.1MnO3 (<50 nm), grown on a (100) face of SrTiO3 substrate. For the thicker films (>50 nm), similar to the single crystal, no such transition is observed below TC. Additionally, we observe the suppression of the features associated with charge or orbital ordering in intentionally La-deficient thin films of La0.88Sr0.1MnO3 (<75 nm). In thin films, transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 9 publications
7
74
0
Order By: Relevance
“…Compressive strain usually reduces the resistivity and shifts T C towards higher temperature. These effects have been confirmed in La 0.7 Ca 0.3 MnO 3 films 6,7 and La 0.7 Sr 0.3 MnO 3 films [8][9][10][11][12] grown on various substrates.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Compressive strain usually reduces the resistivity and shifts T C towards higher temperature. These effects have been confirmed in La 0.7 Ca 0.3 MnO 3 films 6,7 and La 0.7 Sr 0.3 MnO 3 films [8][9][10][11][12] grown on various substrates.…”
Section: Introductionmentioning
confidence: 65%
“…In epitaxial films, biaxial strain has been reported to have very strong effect on the changes in T C and insulator-metal transition temperature (T IM ) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Several publications have reported that both T C and T IM can vary with film thickness [14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the material property can be altered by the epitaxial strain through the strong couplings in TMO between the charge, spin, orbital, and lattice degrees of freedom [10,11]. For example, previous studies have shown that the superconducting [12,13], ferromagnetic (FM) [14], and metal-insulator transition temperature [15][16][17] can be controlled by the strain.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the thick film (240 nm) shows the bulk-like behavior with a metalinsulator transition, T MI , at 220K followed by a transition to a charged ordered insulator at 170K, charge ordering is destroyed in the homogeneously strained thin films. Compressive epitaxial strain causes here the transition from a ferromagnetic insulator to a ferromagnetic metal [4]. Similarly, in thin films of the charge-ordered [CO] Pr 1/2 Ca 1/2 MnO 3 the robustness of the CO state depends strongly on the strains and thus on the film thickness as shown by Prellier et al [8] .…”
Section: Tailoring Epitaxial Strain In Hts Thin Filmsmentioning
confidence: 81%